2021
DOI: 10.1038/s41467-021-21730-2
|View full text |Cite
|
Sign up to set email alerts
|

Graded recruitment of pupil-linked neuromodulation by parametric stimulation of the vagus nerve

Abstract: Vagus nerve stimulation (VNS) is thought to affect neural activity by recruiting brain-wide release of neuromodulators. VNS is used in treatment-resistant epilepsy, and is increasingly being explored for other disorders, such as depression, and as a cognitive enhancer. However, the promise of VNS is only partially fulfilled due to a lack of mechanistic understanding of the transfer function between stimulation parameters and neuromodulatory response, together with a lack of biosensors for assaying stimulation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 69 publications
6
85
1
Order By: Relevance
“…Interesting in this respect is that extinction studies in rats with positive results used longer pulse widths compared to the human extinction studies with taVNS (500 vs 250 μs; e.g., Peña et al, 2013Peña et al, , 2014. Findings from iVNS in rats also showed that longer pulse widths and higher intensities drive greater LC firing rates and pupil size (Hulsey et al, 2017;Mridha et al, 2021). taVNS studies do not typically manipulate pulse width (i.e., 200-250 μs) and frequency (i.e., 25 Hz), probably because commonly used devices (e.g., NEMOS) only allow for the modification of intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Interesting in this respect is that extinction studies in rats with positive results used longer pulse widths compared to the human extinction studies with taVNS (500 vs 250 μs; e.g., Peña et al, 2013Peña et al, , 2014. Findings from iVNS in rats also showed that longer pulse widths and higher intensities drive greater LC firing rates and pupil size (Hulsey et al, 2017;Mridha et al, 2021). taVNS studies do not typically manipulate pulse width (i.e., 200-250 μs) and frequency (i.e., 25 Hz), probably because commonly used devices (e.g., NEMOS) only allow for the modification of intensity.…”
Section: Discussionmentioning
confidence: 99%
“…However, while it would be intriguing to see whether pupil size changes co-varying with emotional activation or mental effort predict detection performance in a similar way to that found here, the extent of such pupil size variation might be too small to see an effect on visual detection performance. Stimulation of the vagus nerve might provide an alternative to manipulate pupil size; however, evidence is conflicting here with many null results also reported (Mridha et al, 2021, reports such effects in mice; but see also Burger et al, 2020;Keute et al, 2019;Warren et al, 2019, for no such effects in humans). Further, since small finger movements like pressing a button already produce reliable and substantial pupil size changes (Richer & Beatty, 1985;Strauch et al, 2020), more intense movements like continuously tapping with a hand or a foot might induce sufficiently large pupil sizes.…”
Section: Discussionmentioning
confidence: 63%
“…a readout of VNS efficacy (Mridha et al 2021). Thus, these results provide evidence that changes in the activity of A1 neurons following VNS-sound pairing are mediated by two pathways (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous fluctuations in pupil size are correlated with changes in sensory cortical activity (McGinley et al 2015;Vinck et al 2015) and track rapid changes in activity of adrenergic and cholinergic axon terminals in cortex (Reimer et al 2016). Pupil dilation has also been observed following VNS (Bianca and Komisaruk 2007;Desbeaumes Jodoin et al 2015) and has been proposed as a biomarker for effective stimulation (Mridha et al 2021).…”
Section: Pupil Dilation and Gating Of Long-term Vns Effectsmentioning
confidence: 99%